Impact of Plasma Epstein-Barr Virus-DNA and Tumor Volume on Prognosis of Locally Advanced Nasopharyngeal Carcinoma. (31st January 2015) - Chen, Meng; Yin, Li; Wu, Jing; Gu, Jia-Jia; Jiang, Xue-Song; Wang, De-Jun; Zong, Dan; Guo, Chang; Zhu, Huan-Feng; Wu, Jian-Feng; He, Xia; Guo, Wen-Jie
Abstract : This retrospective study aims to examine the association of plasma Epstein-Barr virus- (EBV-) DNA levels with the tumor volume and prognosis in patients with locally advanced nasopharyngeal carcinoma (NPC). A total of 165 patients with newly diagnosed locally advanced NPC were identified from September 2011 to July 2012. EBV-DNA was detected using fluorescence quantitative polymerase chain reaction (PCR) amplification. The tumor volume was calculated by the systematic summation method of computer software. The median copy number of plasma EBV-DNA before treatment was 3790 copies/mL. The median gross tumor volume of the primary nasopharyngeal tumor (GTVnx), the lymph node lesions (GTVnd), and the total GTV before treatment were 72.46, 23.26, and 106.25 cm 3, respectively; the EBV-DNA levels were significantly correlated with the GTVnd and the total GTV (P < 0.01 ). The 2-year overall survival (OS) rates in patients with positive and negative pretreatment plasma EBV-DNA were 100% and 98.4% (P = 1.000 ), and the disease-free survival (DFS) rates were 94.4% and 80.8% (P = 0.044 ), respectively. These results indicate that high pretreatment plasma EBV-DNA levels in patients with locally advanced NPC are associated with the degree of lymph node metastasis, tumor burden, and poor prognosis.